Analisis Pengendalian Kualitas dalam Upaya Meminimalisasi Tingkat Kerusakan Produk Gula Rafinasi - Faris Ghiyats; Fadila Marga Saty; Dewi Riniarti (Politeknik Negeri Lampung, 2020)
Non-conformance occurs due to unavoidable production process, and there is need to reduce the potential occurrences as well as provide a solution to minimize the level of mismatch. This study aims to identify the percentage and types of discrepancy experienced, by analyzing process capabilities and identify underlying factors in inconsistency. The research was performd in May 2018 at the department of process PT Sugar Labinta, Tanjung Sari, Lampung Selatan. Furthermore, analysis involved the six sigma method with a structured DMAIC approach, while the tools used include check sheet, caused diagram, p-control chart, and Pareto diagram. The results were then processed with the Minitab 18 software, which demonstrated the level sigma process in PT Sugar Labinta to be 5,04 with a DPMO of 238,32. The table of achievement indicates the company performance to be at an average level, in contrast with industries in the USA. However, the level of Sigma 6 is attainable under the circumstances where product-related inconsistences do not exceed 8 tonnes per month.